Ehlers–Danlos Syndrome: Not Just Joint Hypermobility - Tina Bregant; Milica Klopcic Spevak (Case Reports in Medicine)
Ehlers–Danlos syndrome is an umbrella term for a group of heritable soft connective tissue disorders which is characterized by joint hypermobility, skin texture and elasticity abnormalities, and visceral and vascular fragility or dysfunctions. As the syndrome is rare, it is often underdiagnosed. Patients usually present late, with chronic moderate to severe pain which is attributed to the joint hypermobility and joint subluxations. If the clinician is aware of the syndrome, he/she can identify affected patients in order to prevent complications. We report a 60-year-old woman with arthralgia and back pain lasting for several months and recent metatarsophalangeal luxation of the left toe who was discovered to have Ehlers–Danlos syndrome.